Emotional games: How coaches' emotional expressions shape players' emotions, inferences, and team performance. (March 2019) - van Kleef, Gerben A.; Cheshin, Arik; Koning, Lukas F.; Wolf, Svenja A.
Abstract: Objectives: Sports games are inherently emotional situations. Although a plethora of research has investigated how athletes' emotions influence their own performance, scant attention has been paid to how one person's emotional expressions influence others in the sports context. In particular, it remains unclear whether and how sports coaches' emotional expressions influence players. Drawing on emotions as social information (EASI) theory, we examined how coaches' emotional expressions influence players' affect, cognition, and behavior. Design: We conducted two multi-level, multi-source field studies of sports coaches and players engaged in competitive team sports. Study 1 had a cross-sectional research design, and Study 2 had a cross-lagged design involving three measurement points (before, during, and after the game). Method: Study 1 was set in the context of baseball/softball, and study 2 in the context of soccer. In both studies, coaches reported on their emotional expressions, players reported on their experienced emotions and inferences regarding team performance, and the team's actual performance was recorded. Results: Coaches' expressions of happiness and anger predicted (1) players' experiences of happiness and anger, (2) players' inferences about the quality of their performance, and (3) objective team performance outcomes. Regarding team performance, results indicated that coaches' expressions of happiness were conducive to team performance, whereas expressions of anger were not. Conclusions: The current results provide first-time quantitative evidence for the beneficial effects of coaches' positive emotional expressions on sports performance. The findings support key tenets of EASI theory and have implications for the broader literature on coaching and leadership. Highlights: We examined how coaches' emotional expressions influence players. We derived hypotheses from Emotions as Social Information (EASI) theory. We tested the hypotheses in the context of baseball and soccer matches. Coaches' emotion expressions predicted players' emotions and performance inferences. Coaches' pre-game happiness expressions had a positive impact on team performance.